2021
DOI: 10.1017/s0025100321000013
|View full text |Cite
|
Sign up to set email alerts
|

Articulation of geminate obstruents in the Ikema dialect of Miyako Ryukyuan: A real-time MRI analysis

Abstract: The Ikema dialect of Miyako Island in Okinawa, Japan, has typologically rare word-initial and voiced geminate obstruents (e.g. /vva/ ‘you’, /ffa/ ‘child’, /tta/ ‘tongue’, /badda/ ‘side’). These sounds are marked in two ways: Voicing through geminate obstruents is hard to produce and initial voiceless plosives seem to be difficult to perceive. This study investigated real-time magnetic resonance imaging (rt-MRI) to examine the articulatory settings underlying contrasts between singleton and geminate obstruents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…It is known that adult speakers' pronunciation tends to have an accent when they learn to speak a foreign or second language (Archibald, 2021). The basis for a foreign accent is mispronunciations that lead to the perception of a segmental sound substitution (Fujimoto, Shinohara, & Mochihashi, 2021). However, this does not necessarily mean that the perception of a foreign accent is based on easily detectable mispronunciations of vowels and consonants.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that adult speakers' pronunciation tends to have an accent when they learn to speak a foreign or second language (Archibald, 2021). The basis for a foreign accent is mispronunciations that lead to the perception of a segmental sound substitution (Fujimoto, Shinohara, & Mochihashi, 2021). However, this does not necessarily mean that the perception of a foreign accent is based on easily detectable mispronunciations of vowels and consonants.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, vocal-fold slackening allows for a passive expansion of the vocal-tract volume, allowing the airflow to pass through the glottis. Along these lines, Fujimoto and Shinohara (2015) in their real-time MRI study have found pharyngeal expansion in voiced obstruents /z/ and /zz/ but not in the voiceless counterparts in the Miyakojima Ikema dialect of Ryukyuan, presumably because the expansion facilitated vocal-fold vibration.…”
Section: Underlying Mechanisms Of Cf0mentioning
confidence: 98%